The pro-metastatic effects of hemodynamic shear stress : breast cancer cells acquire aggressiveness during circulation - Ma, Shijun (2018)
Cancer metastasis is defined as the spread of cancer cells from the origin site to other parts of the body and is accountable for ninety percent of deaths from solid tumors. Circulation of cancer cells in blood stream is a vital step for distant metastasis, during which cancer cells are exposed to hemodynamic shear stress. It has been well studied that shear stress can damage circulating tumor cells (CTCs), however, the other actions of shear stress on tumor cells, and how shear stress modulates functions and properties of tumor cells are not understood. Based on the hypothesis that hemodynamic shear stress may enhance invasiveness of circulating tumor cells to assist them in exiting blood flow and invading secondary tissues, this thesis explores the pro-metastatic effects of shear stress. By using a novel microfluidic circulatory system, I applied physiological fluidic shear stress on breast cancer cells and demonstrated that an arterial level of shear stress significantly enhanced tumor cell migration in transwell and wound healing assays. The results from an in vitro transendothelial assay indicated that extravasation of tumor cells was increased by shear stress treatment. The mechanism study revealed that fluidic shear stress elevated the intracellular levels of reactive oxygen species (ROS), which is an early and indispensable event for increasing phosphorylation level of the extracellular signal-regulated kinases (ERK1/2). Subsequently, phosphorylated ERK1/2 promoted migration of tumor cells, which enhanced extravasation. I found that reducing cellular ROS production by antioxidants suppressed tumor cell extravasation in both in vitro transendothelial assay and in vivo zebrafish model. I further explored the upstream signaling pathways and identified MnSOD in the mitochondria as an important regulator that mediates the shear stress-promoted tumor cell migration. Fluidic shear stress can induce tumor cells to generate mitochondrial superoxide, which is the major form of cellular ROS. MnSOD converts superoxide into hydrogen peroxide, which can diffuse into the cytosol and activate ERK1/2 to stimulate cell migration. Here, I verified that MnSOD played a vital role in shear stress-promoted tumor cell migration, by regulating the conversion and distribution of cellular ROS. In addition to migration and extravasation, I investigated the other functions of circulated tumor cells and found that shear stress was able to enhance the adherence of tumor cells to extracellular matrix (ECM), as well as endothelial monolayer. The elevated cellular ROS level played important roles in shear stress-enhanced tumor cell adhesion, by promoting phosphorylation of focal adhesion kinase (FAK). Overall, this study presents experimental evidence on the pro-metastatic effects of hemodynamic shear stress and reveals the underlying mechanism. Understanding how fluidic shear stress influences aggressiveness of tumor cells provides new insights into the origins and nature of cancer metastasis and have important implications in cancer treatment. Based on the study, I have identified different signaling molecules in the related pathway, including MnSOD, ROS, ERK1/2 and FAK, which can be used as the potential therapeutic targets for suppressing metastasis and tumor progression.